Study on Factors Affecting the Performance of a CRISPR/Cas-Assisted New Immunoassay: Detection of Salivary Insulin as an Example - Lin, Xiaoting; Wang, Gonglei; Ma, Long; Liu, Guozhen (Frontiers in Bioengineering and Biotechnology, 2021)
The clustered regularly interspaced short palindromic repeat (CRISPR)/Cas is now playing a significant role in biosensing applications, especially when the trans cleavage activity of several Cas effectors is discovered. Taking advantages of both CRISPR/Cas and the enzyme-linked immunosorbent assay (ELISA) in analytical and clinical investigations, CRISPR/Cas powered ELISA have been successfully designed to detect a spectrum of analytes beyond nucleic acid. Herein, we developed a CRISPR/Cas12a assisted new immunoassay (CANi) for detection of saliavary insulin as an example. Specifically, factors (antibody selection, temperature, assay time, et al.) affecting the CRISPR/Cas-based ELISA system's performance were investigated. It was observed that the concentration of blocking solution, selection of the capture antibody pairs, the sequences of triggering ssDNA and guiding RNA affected this immunoassay sensitivity. In contrast, the pre-incubation of CRISPR/Cas12a working solution and pre-mixture of detection antibody with anti-IgG-ssDNA did not show influence to the performance of CANi for the detection of insulin. Under the optimised conditions, the sensitivity for detection of salivary insulin was 10 fg/mL with a linear range from 10 fg/mL to 1 ng/mL.